Algunas ideas sobre la univocidad escotista - Brando, Juan (Sapientia, 2019)
This essay shows, in the first place, a critical examination of the arguments in favor of the uniqueness of being, present in the work of Scoto Opus oxoniense, considering, especially, the analysis made by Etienne Gilson in his book Jean Duns Scot. The treatment of the question of univocity allows tangential observations about the problems of the knowability of God and the primary object of human understanding. Later, there is a debate on the status of being and of determinations in the framework of the theory of univocity, and the imputation that being can be identified with gender, or considered a mere being of reason. Subsequently, the position of an author who considers that Scoto pointed out, in "Very subtle questions", opinions about the univocity and the object of metaphysics, which differ from those contained in the Oxonian Commentary. The final paragraphs are a reflection on philosophy in relation to the natural state of man and its consequences for the way of considering metaphysics against theology, a prominent issue to understand the general meaning of Scotism.